Human naive and memory T lymphocytes differ in telomeric length and replicative potential. - Weng, N P (1995)
The present study has assessed the replicative history and the residual replicative potential of human naive and memory T cells. Telomeres are unique terminal chromosomal structures whose length has been shown to decrease with cell division in vitro and with increased age in vivo for human somatic cells. We therefore assessed telomere length as a measure of the in vivo replicative history of naive and memory human T cells. Telomeric terminal restriction fragments were found to be 1.4 +/- 0.1 kb longer in CD4+ naive T cells than in memory cells from the same donors, a relationship that remained constant over a wide range of donor age. These findings suggest that the differentiation of memory cells from naive precursors occurs with substantial clonal expansion and that the magnitude of this expansion is, on average, similar over a wide range of age. In addition, when replicative potential was assessed in vitro, it was found that the capacity of naive cells for cell division was 128-fold greater as measured in mean population doublings than the capacity of memory cells from the same individuals. Human CD4+ naive and memory cells thus differ in in vivo replicative history, as reflected in telomeric length, and in their residual replicative capacity.